Mentoring and Social Work: Paths of Reception and Integration in College Education: https://doi.org/10.60543/ts_iss.vi9.10898 ("Temas Sociais" Journal, 2025)
This essay presents a practical synthesis of the Mentoring Program of the Institute of Social Work of the Lusófona University, focusing on the role of the student mentor as an agent of reception, integration and promotion of academic success. The document explores the structuring objectives of the program, highlighting the importance of peer support in the process of adaptation to higher education, as well as the development of socio-emotional, communicational and relational skills that are fundamental for the integral formation of students. The mentor-mentee relationship is also analyzed as an element of trust, empathy and mutual growth, underlining the relevance of this practice for the construction of a more inclusive, humane and collaborative academic culture. Some testimonies from former mentors of the program are also presented. The text concludes by reinforcing the contribution of mentoring to the strengthening of the university community and to the realization of the values of Social Work in the educational context.
Keywords: Social work; Mentoring; Integration; Reception.